Nano- and microgels: a review for educators - Zhilin Denis M.; Pich Andrij (Chemistry Teacher International, 2021)
Nano- and microgels are promising soft polymer materials for different application fields: stabilizers, sensors, catalysts, selective sorbents, drug delivery carriers etc. They are composed of cross-linked polymer chains swollen with a solvent. The building blocks, synthesis approaches and architecture of nano- and microgels are reviewed. The mechanisms of responsiveness to various stimuli are described, examples of applications are provided. Micro- and nanogels are good objects for learning projects and the ideas for learning projects with microgels are described.